THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT CIMB BANK, SOLOK CITY WEST SUMATERA - yanti, rini parmila; M, Yeni; Yuliana, Sartia (International Journal of Social Science and Business, 2019)
The objectives to be achieved through this research are as follows: 1). To Learn How to Shape Commercial Service Quality at At CIMB Bank, Solok City West Sumatera .2). To Learn How to Form Customer Satisfaction At CIMB Bank, Solok City West Sumatera. 3). To Learn How to Influence of Service Quality on Customer Satisfaction At Cimb Bank Solok City West Sumatera Influence research on the implementation of service quality on customer satisfaction At CIMB Bank, Solok City West Sumatera. This effect, researchers using survey research method with qualitative and quantitative approaches. From the research results presented the following conclusions: 1) .The quality of service At CIMB Bank, Solok City West Sumatera still less for it needs to be improved again service excellence so that customers feel more comfortable and happy in bertransaksi.2) Satisfaction in the service At CIMB Bank, Solok City West Sumatera should be increased to clients that the service is fast and accurate and easy to transaction At CIMB Bank, Solok City West Sumatera. 3) Based on the results of hypothesis testing results obtained through the correlation between the Influence Quality of service (X) to the satisfaction of the customer (Y) is obtained by 0868, meaning between Quality of service and satisfaction of customers there is a very strong and positive with a significant level less than 0.005, namely of 0000. While the value of determinant coefficient (R-Square) Influence Quality of service X) is equal to 0754, or 75.4%, where the variation increases and decreases in customer satisfaction (Y) can be explained by the variable quality of service Influence of 75.4%, while the remaining 24.8% customer satisfaction influenced by other factors not included in the variables studied. To test the regression Y = a + bX obtained Y = 172+ 0513 (Quality of service), this shows the positive effects generated by the quality of service to the satisfaction of the customer. This means that if the quality of service (X) is increased by 1 point then it will give effect to customer satisfaction for 172+ 0513 Based on the hypothesis test (t test) obtained t count of 12 118 while ttabel amounted to 1,671. Thus t count 12 118> ttable 1671, so the hypothesis (Ho) is rejected and (Ha) received acceptable. This means that there is the influence of service quality on customer satisfaction. In connection with the above conclusions, put forward suggestions as follows: 1. To improve the quality of service should be a reform of the Bank as provided briefing for employees and improving facilities for the convenience customers. 2. To increase employee satisfaction can provide the best service to customers so that customers feel comfortable and pleased.3. Based on the results of hypothesis testing there is influence between service quality and customer satisfaction. to see the influence between service quality and customer satisfaction indicators of service need attention